Delirium During Recovery in Patients With Severe COVID-19: Two Case Reports - Han, Dong; Wang, Chenyang; Feng, Xiaojing; Wu, Jing (Frontiers in Medicine, 2020)
Novel coronavirus disease (COVID-19), caused by SARS-CoV-2, has rapidly evolved into a worldwide pandemic, leaving patients with life-threatening respiratory, cardiovascular, and cerebral complications. Here we reported on two patients with severe COVID-19 who experienced delirium in the early stage of recovery and mental illness including fatigue, anxiety, and post-traumatic stress disorder in the post-illness stage of COVID-19. Two patients were admitted to hospital due to clinical symptoms and features of CT and were confirmed for COVID-19 by positive results of a throat swab for SARS-CoV-2. Due to severe respiratory symptoms and a low oxygenation index, they were transferred to the ICU and received invasive mechanical ventilation and sedation. Hyperactive delirium was observed after being transferred out of the ICU. Different treatment measures were taken in time. Delirium did not occur again in hospital, but they showed mental suffering, including fatigue, anxiety, and post-traumatic stress disorder (PTSD), during the 5 month follow-up after discharge.